The Indonesian Orthodontists’ Perceptions about malocclusion and postural in Diagnosis: Survey analytic of Malocclusion and posture - Sofyanti, Ervina; Manurung, Prans Samuel Antony; Purbiati, Maria; Farmasyanti, Cendrawasih Andusyana; Mardiati, Endah; Narmada, Ida Bagus; Alhasyimi, Ananto Ali (Indonesian Journal of Medical Anthropology, 2025)
The relationship between dental occlusion and posture remain controversial due to the lack of clear cause-and-effect evidence. Scientifically validated and reliable evidence can shape individuals’ perceptions and influence their decisions regarding orthodontic treatment. This study aimed to conduct a survey to assess Indonesian orthodontists’ perceptions regarding the relationship between malocclusion and posture (both oral and body posture) based on gender and years of professional experience. An online survey was conducted involving orthodontists who attended the Orthodontic Meeting in November based on a 7-item Likert scale modified questionnaire. Levene’s test was performed continued with a prerequisite for the Multivariate Analysis of Variance test (p<0.05). The perceptions of 214 active members of the Indonesian Orthodontist Association showed a positive agreement regarding the relationship between malocclusion and posture (both oral and body). There was no significant interaction between gender and perception (p=0.417), nor between years of professional experience as an orthodontist and perception (p=0.182) regarding the relationship between malocclusion and posture. Since this survey-based analytical study found no interaction between gender and years of professional experience in orthodontists’ agreement on the premise, these findings should be considered when updating the standard operating procedures curriculum for orthodontic diagnosis and multidisciplinary orthodontic approaches. Keyword: Perception, Orthodontist, Malocclusion, Posture